The Role of the Heart Team in Patients with Diffuse Coronary Artery Disease Undergoing Coronary Artery Bypass Grafting - Dourado, Luciana Oliveira Cascaes; Pereira, Alexandre C.; Poppi, Nilson Tavares; Cavalcante, Rafael; Gaiotto, Fabio; Dallan, Luis Alberto Oliveira; Bittencourt, Marcio Sommer; Cesar, Luiz Antonio M.; Gowdak, Luis Henrique W. (The Thoracic and Cardiovascular Surgeon, 2020)
Background In patients eligible for coronary artery bypass grafting, no data assess the importance of the Heart Team in programming the best surgical strategy for patients with diffuse coronary artery disease (CAD). This study aims to determine the contribution of the Heart Team in predicting the feasibility of coronary artery bypass graft and angiographic surgical success in these patients based on visual angiographic analysis.Methods Patients with diffuse and severe CAD undergoing incomplete coronary artery bypass graft surgery were prospectively included. One-year postoperative coronary angiograms were obtained to evaluate graft occlusion. Two clinical cardiologists, two cardiovascular surgeons, and one interventional cardiologist retrospectively analyzed preoperative angiograms. A subjective scale was applied at a single moment to quantify the chance of successful coronary artery bypass grafting for each coronary territory with anatomical indication for revascularization. Based on individual scores, the Heart Team's and the specialists' scores were calculated and compared.Results The examiners evaluated 154 coronary territories, of which 85 (55.2%) were protected. The Heart Team's accuracy for predicting the angiographic success of the surgery was 74.9%, almost equal to that of the surgeons alone (73.2%). Only the interventional cardiologist predicted left anterior descending territory grafting success. The Heart Team had good specificity and reasonable sensitivity, and the surgeons had high sensitivity and low specificity in predicting angiographic success.Conclusion The multispecialty Heart Team achieved good accuracy in predicting the angiographic coronary artery bypass graft success in patients with diffuse CAD, with a high specificity and reasonable sensitivity.
Keywords: CABG; vascular graft; coronary artery disease; Heart Team; outcomes